2009
DOI: 10.1556/monkol.53.2009.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Az emberi májrák komparatív genomikai osztályozása

Abstract: Global transcriptome analysis has been successfully applied to characterize various human tumors, including hepatocellular carcinomas. This novel technology can facilitate early diagnosis, as well as prognostic and therapeutic diversification of cancer patients. To enhance access to the genomic information buried in archived pathology samples, we assessed RT-PCR amplification rates in paraffin-embedded tissues preserved in three different fixatives. Reliable amplification could be achieved from all paraffin-em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Moreover, high HGF level in serum and deregulated expression of c-Met in HCCs are closely associated with early recurrence [ 20 ] and patients with high c-Met expressing HCCs usually have shorter 5-year survival rate after curative surgical resection [ 19 22 ]. In addition, a group of HCCs (27%) with a c-Met-induced transcriptional signature was characterized by a higher rate of vascular invasion [ 23 ]. In vitro studies have also revealed the effects of HGF on metastatic changes of HCC, including EMT, migration, and invasion [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high HGF level in serum and deregulated expression of c-Met in HCCs are closely associated with early recurrence [ 20 ] and patients with high c-Met expressing HCCs usually have shorter 5-year survival rate after curative surgical resection [ 19 22 ]. In addition, a group of HCCs (27%) with a c-Met-induced transcriptional signature was characterized by a higher rate of vascular invasion [ 23 ]. In vitro studies have also revealed the effects of HGF on metastatic changes of HCC, including EMT, migration, and invasion [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the fifth common cancer worldwide whose mortality rate parallels with its incidence [ 1 ]. Rapid growth and early vascular invasion are the most important characteristics of HCC [ 2 - 4 ]. The treatment options for HCC depend on the stages and grades of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Zou et al demonstrated that crizotinib, a non-specific MET TKI, which is currently in phase III clinical trial for the treatment of non-small cell lung cancer, was able to inhibit in vitro tubulogenesis of primary endothelial cells [25]. As potential interplay between aberrant MET signaling and angiogenesis in HCC, a study by Kaposi-Novak reported a MET aberrant expression-related transcriptional signature in a group of HCCs that were characterized by higher rate of vascular invasion and increased microvessel density [26], emphasizing therefore the potential role of MET-related angiogenesis in the pathogenesis of these tumors.…”
Section: Introductionmentioning
confidence: 99%